LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Fajri, Saiful; Wahyuni, Ika; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Company value in mining companies listed on the Indonesia Stock Exchange with Profitability as an Intervening variable. Companies with good performance will continue to experience growth well in the future. Company size is considered capable of affecting company value. The company's goal is to increase prosperity and profits for shareholders in the company. This study aimed to determine the significance of the effect of Leverage and company size on company value through Profitability. This research uses descriptive and quantitative research. The population in this study are 47 mining sector companies listed on the Indonesia Stock Exchange period 2019-2021. The sampling technique in this study used Purposive Sampling technique. Data analysis and hypothesis testing in this study. This study uses the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that Leverage has a negative but insignificant effect on Profitability, Company size has a negative but insignificant effect on Profitability, Leverage has a negative but insignificant effect on Company value, Company size has a significant positive effect on company value, Profitability has a positive but insignificant effect on company value. The indirect effect hypothesis test results show that the variable Leverage on Company value through Profitability has a negative but insignificant effect, and company size on Company value through Profitability has a negative but insignificant effect.